Faktor-Faktor Biaya Pemulihan Pengelolaan Sumber Daya Air - Sri Sangkawati (Department of Civil Engineering, Diponegoro University, 2009)
To ensure sustainability of the benefits of water resources and water resources infrastructure for managing the funds should be provided adequately. Adequacy of funding for management can be planned based on the principle of full cost recovery or O & M cost recovery. One source of funding for the management of water resources as regulated in article 77, UU.RI Number 7, 2004 are the beneficiaries of which are service fees for water resources management (BJP-SDA). In order to realize the management of water resources with the principle of demand-side management and increase service fees for water resources management, it is necessary to analysis the correlation between the cost of management services to beneficiaries in accordance with existing regulations, commitment, and the contribution fee to be determined need to obtain agreement from interested parties (stakeholders) with the criteria that must be met. Important factors for the realization of cost recovery for water resources management in a basin area are: recovery policy management costs that will be done whether on the principle of full cost recovery or the O& M cost recovery, user groups according to water rights and the economic benefits derived each group of beneficiaries of development and management of water resources. Cost recovery model should be built at least with respect to these important factors. Keywords : cost recovery, users Abstrak Untuk menjamin kelestarian manfaat sumber daya air serta sarana dan prasarana keairan maka dana untuk pengelolaannya perlu disediakan secara memadai. Kecukupan dana untuk pengelolaan dapat direncanakan berdasarkan prinsip full cost recovery maupun O&M cost recovery. Salah satu sumber dana untuk pengelolaan sumber daya air sebagaimana diatur dalam pasal 77, UU Nomor 7 tahun 2004 adalah dari para penerima manfaat yang merupakan biaya jasa pengelolaan sumber daya air (BJP-SDA). Guna mewujudkan pengelolaan sumber daya air dengan prinsip demand-side management dan meningkatkan penerimaan biaya jasa pengelolaan sumber daya air, maka perlu dilakukan analisis korelasi antara biaya jasa pengelolaan dengan penerima manfaat sesuai dengan peraturan yang berlaku, komitmen bersama, dan besarnya kontribusi biaya yang akan ditetapkan perlu memperoleh kesepahaman dari pihak-pihak yang berkepentingan (stakeholders) dengan kriteria yang harus dipenuhi. Faktor-faktor penting untuk realisasi pemulihan biaya pengelolaan sumber daya air di dalam satu wilayah sungai adalah: kebijakan pemulihan biaya pengelolaan yang akan dilakukan apakah berdasarkan prinsip full cost recovery atau O&M cost recovery, kelompok pemanfaat sesuai dengan hak atas air dan nilai manfaat ekonomi yang diperoleh masing-masing kelompok pemanfaat dari kegiatan pengembangan dan pengelolaan sumber daya air. Model pemulihan biaya harus dibangun sedikitnya dengan memperhatikan faktor-faktor penting tersebut. Kata kunci: biaya pemulihan, kelompok pemanfaat